Knowledge, attitude and practices of antibiotic usage among students from Mumbai University - Limaye, Dnyanesh; Naware, Sanika; Bare, Priyanka; Dalvi, Shreya; Dhurve, Ketaki; Sydymanov, Arlan; Limaye, Vaidehi; Pitani, Ravi Shankar; Kanso, Zeinab; Fortwengel, Gerhard (International Journal of Research in Medical Sciences, 2018)
Background: Discovery of antibiotics have helped to manage the devastating diseases. Presently, the antibiotic era is threatened by the emergence of high level of antibiotic resistance of important pathogens. Misuse of antibiotics poses a serious risk to infectious disease control. It is necessary to improve public awareness to bring a change in the behavior of consumers. Therefore, present study was undertaken to assess the existing knowledge, attitude and practices related to antibiotic usage among university students. Methods: A cross-sectional study was carried out among students from Mumbai University, India during May-June 2017. 300 students were approached to participate in the study of which 250 agreed to participate (males: 117; females: 133). Pretested questionnaire was distributed and collected data was analyzed using IBM SPSS version 23. Results: Substantial number (33% and 40%) participants were unaware about the differences in antibiotic-anti-inflammatory drugs and antibiotic-antipyretics respectively. 28% of the participants thought it is right to stop antibiotics only based on symptoms improvement. Sixty eight percent and seventy nine percent participants believed that antibiotics should always be prescribed to treat flu like symptoms and pneumonia respectively. Conclusions: Participants demonstrated poor knowledge about antibiotics. Similarly, their attitude and practice toward antibiotic use was associated with misconceptions. An educational intervention can be introduced to make them aware about rational antibiotic practices.